Films with a message on biodiversity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A picture speaks a thousand words, to be sure, but when a collection of some of the world s best pictures is combined with high quality words, the effect is outstanding. The Moving Pictures catalogue is the flagship publication of the Television...